Anti-Onchocercal Properties of Extracts of Scoparia dulcis and Cylicodiscus gabunensis - Tiku Edward Tiku; Moses Samje; Napoleon Mfonku; Fidelis Cho-Ngwa (Journal of Tropical Medicine)
Introduction. The elimination of onchocerciasis is hampered by the absence of suitable drugs that are effective against adult filariae. This study is aimed at assessing the anti-onchocercal effects of extracts of Scoparia dulcis and Cylicodiscus gabunensis that could serve as drug leads against onchocerciasis. Methods. Different parts of the plants (Scoparia dulcis and Cylicodiscus gabunensis) were extracted with hexane, methylene chloride, and methanol. The extracts were tested in vitro against the bovine model parasite, Onchocerca ochengi. Adult female worm viability was determined biochemically by MTT/formazan colorimetry, while the adult male and microfilariae viability were determined by microscopy based on % inhibition of worm motility score. Cytotoxicity and acute toxicity of active extracts were tested on monkey kidney epithelial cells (LLC-MK2) and Balb/C mice, respectively. Results. The hexane extract of Scoparia dulcis recorded the highest activity, with IC50s of 50.78 μg/ml on both adult male and female worms and 3.91 μg/ml on microfilariae. For Cylicodiscus gabunensis extract, the highest activity was seen with the methylene chloride extract, with IC50s of 50.78 μg/ml, 62.50 μg/ml, and 16.28 μg/ml on, respectively, adult male, female, and microfilariae. The 50% cytotoxic concentration on the LLC-MK2 cells was 31.25 μg/ml for the most active extracts. No acute toxicity was recorded for the extracts. Phytochemical analysis of the extracts revealed the presence of alkaloids, flavonoids, sterols, saponins, phenols, and glycosides. Conclusion. This study validates the traditional use of these plants in treating onchocerciasis and suggests S. dulcis and C. gabunensis as new potential sources for the isolation of anti-onchocerca lead compounds.